2021
DOI: 10.1126/science.abd7645
|View full text |Cite
|
Sign up to set email alerts
|

A nearby transiting rocky exoplanet that is suitable for atmospheric investigation

Abstract: Spectroscopy of transiting exoplanets can be used to investigate their atmospheric properties and habitability. Combining radial velocity (RV) and transit data provides additional information on exoplanet physical properties. We detect a transiting rocky planet with an orbital period of 1.467 days around the nearby red dwarf star Gliese 486. The planet Gliese 486 b is 2.81 Earth masses and 1.31 Earth radii, with uncertainties of 5%, as determined from RV data and photometric light curves. The host star is at a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
6
3
1

Relationship

6
4

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 96 publications
0
30
0
Order By: Relevance
“…This technique overcomes the difficulty of low mutation sensitivity, as well as the inability to decipher the changing details of tumor subtypes, which contributes to tracking the spread pattern and key genes in lung cancer. These novel findings indicated the potential for developing targeted therapy and improving the clinical management of lung cancer in patients with KRAS mutations [ 41 ]. Another study in which scRNA-seq and high-confidence clonal tracing were combined demonstrated the first detailed characterization of leukemic stem cells, shedding new light on the understating of leukemia oncogenesis and treatment [ 42 ].…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…This technique overcomes the difficulty of low mutation sensitivity, as well as the inability to decipher the changing details of tumor subtypes, which contributes to tracking the spread pattern and key genes in lung cancer. These novel findings indicated the potential for developing targeted therapy and improving the clinical management of lung cancer in patients with KRAS mutations [ 41 ]. Another study in which scRNA-seq and high-confidence clonal tracing were combined demonstrated the first detailed characterization of leukemic stem cells, shedding new light on the understating of leukemia oncogenesis and treatment [ 42 ].…”
Section: Emerging Single-cell Sequencing Technologiesmentioning
confidence: 99%
“…We performed intensive radial velocity observations of this planet in May 2020, which lead to a mass measurement better than 5% (limited by the uncertainty in the mass of the host star) and a 1σ error on the predicted secondary eclipse time of only 12 minutes. 28 Data from the red arm of MAROON-X have a RMS of 44 cm s −1 , significantly outperforming other RV instrument observing this target. When combining the blue and red arms and binning the data over 30 minutes the RMS falls to <30 cm s −1 .…”
Section: On-sky Rv Performancementioning
confidence: 90%
“…Each of these three basic methods is addressed in subsequent discussion. If concurrent radial velocity and transient methods measurements are available, this combination can be used to determine the planet's mass, radius, and density [23,33].…”
Section: Detection Methodsmentioning
confidence: 99%